Island of Mayotte on its way to the international community - Ivan Victorovich Nezhentsev; Lyudmila Vasil’evna Ponomarenko (Vestnik RUDN. International Relations, 2017)
The article devoted to the analysis of change of status of Mayotte with signing of the Treaty on the possession of Mayotte to France in 1841 continuing until Mayotte’s departmentalization in 2011. Relations between France and Mayotte are essentially different from traditional cooperation “Metropolitan-colony”, due the fact that Mayotte was an important strategic territory of France in the Indian Ocean since 19th century. The article contains the detail analysis of specifics features of French colonial administration. The legislative changes of territorial status of Mayotte traced on the basis of researched decrees, laws, resolutions. The status of Mayotte had changed with the expansion of the colonial Empire: from autonomy up until 1912, to the dependent and controlled up until 1946. In the next 20 years Mayotte crosses swords for the expansion of autonomy from France. Besides it, in this chapter of the article considers the processes of formation of various people's movements, such as “Mouvement du peuple mahorais”, which purposed to get from metropolitan France the status of the French Overseas territory. After the fall of the colonial system, France tried to prevent the final breakdown of the Empire, for that French Republic takes root intro their colonies in a structure of France by legislation. In 1975 Comoros gained independence, and entered immediately into a confrontation with France with regard to Mayotte. The international community headed by the UN required return the island to the Comoros, despite it France referred to a popular referendum during which the residents of Mayotte had expressed a desire to be a part of France. Hurriedly, France granted to Mayotte the status of the Overseas community of France. Despite the new status, Mayotte continued to be a backward region of France up until 1990s. In the 21st century starts a new period of changes. There is an active development of the island in such spheres as administration management, economy, culture and social integration with metropolitan France which ultimately will lead to the departmentalization in 2011. The conclusion examines the processes of integration of Mayotte with France and the EU after departmentalization, prospects of development and reinforcement of role of the island as a political and economic zone of France in East Africa.